Opinions of Educational Experts in Shahid Beheshti University of - Abed Saeedi, Zhila; Manoochehri, Houman; Moslemi, Azam (Advances in Nursing & Midwifery, 2015)
Background and aim: Education and clinical application of basic science is important in nursing education , nurse educators have reported problems with the teaching and learning of bioscience. This study aimed to explore educational expert’s opinions regarding the basic science courses offer. Materials and methods: This descriptive study was performed on 35 educational experts at Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences. Data were collected with a semistructured questionnaire. Face and content validity were checked. The reliability of the questionnaire was determined using the Cronbach’s Alpha test. Data were analyzed by SPSS(version 18) and descriptive statistics. Findings: 50.0 percent of educational experts agreed with the proportion of basic science courses for nursing course objectives. Also, they agreed with time extension for anatomy and physiology courses, especially these courses offer in several semesters and relevant to clinical nursing courses. Conclusion: According to the results, it seems that curriculum planners should investigate about the clinical application of basic science courses in nursing program as a priority, and fundamental reform needs to consider basic science courses offer, especially anatomy and physiology, as well. Keywords: Curriculum planning, Educational Experts, Nursing education, Basic science courses